Lived Experiences during International Service Learning: A Semiotic Analysis of Photo Journals - Catherine E. Dobbins; Kristin E. Gibson; Leslie D. Edgar; Kim E. Dooley (Journal of International Agricultural and Extension Education, 2020)
International service learning (ISL) is a pedagogical approach used to prepare students to be global citizens and has emerged as a popular short-term program model for international experiences. Few studies of ISL have integrated semiotic photo analysis into their evaluations. Combining students’ photographs with text encourages reflection on knowledge and experiences as well as how they are related. The current study used semiotic analysis to understand the lived experiences of students on an ISL to Guatemala. The participatory nature of the research process was critical to the semiotic analysis, as the researchers had an understanding of the cultural perspectives and traditions that emerged in the images which could have been overlooked by a researcher without knowledge of the specific cultural context. Participants kept a photo journal of 10 images and associated narratives to depict their experiences on the ISL. Both semiotic and content analysis were conducted on each journal entry. Coding yielded nine themes: new perspectives, personal connections, impact of coffee, intercultural comparisons, reality of life in Guatemala, cultural values, impact of ISL, connection to photograph, and sense of place. Combining the semiotic and content analysis yielded concurrent meanings through narrative and visual reflections, which, when combined with the researchers’ participatory knowledge of the experience, informed future ISL projects for the research and teaching team. The combination of visual and narrative methods required students to think about what story they will tell about their experience, and brings new layers of meaning to the reflection process.
Keywords: photo-based methods; experiential education; educational evaluation; Guatemala